THE ROLE OF SPORTS IN ENSURING THE PHYSICAL AND SPIRITUAL DEVELOPMENT OF THE YOUNGER GENERATION - Rakhmatova Dilbar (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the role of sports in ensuring the physical and spiritual well-being of the younger generation. Based on pedagogical data, the author analyzes the problem on the basis of the existing scientific literature and explores the specifics of the role of sports in ensuring the physical and spiritual well-being of the younger generation.